“FRENSS” INSTANT RED GINGER DRINKS BUSINESS IN LUMBAN PINGGOL VILLAGE, PANGURURAN SUB-DISTRICT, SAMOSIR DISTRICT - Mutiara, Erli; Adikahriani, Adikahriani; Siahaan, Riana Friska; Fridiarty, Lelly (Universitas Negeri Medan, 2021)
Bandrek (Ginger Drink) is a traditional drink that has a great demand by consumers because of the health benefits. Most of the traditional beverage production is still produced on a household scale, such as the instant ginger drink produced by the household business “Frenss”. The household businesses that produce ginger drink should apply good food production methods so that the products produced are safe and their nutritional value is also maintained. Lumban Pinggol Village, Pangururan District, Samosir Regency is one of the tourist areas in the Lake Toba area in North Sumatra. One of the residents' efforts is to work on making ginger drink Instant. The processing method for instant ginger drink is still manual, even though the ginger drink produced reaches 50 kg each day. Therefore, the solution offered to partners was to design a ginger grinding machine. The implementation method consists of empowerment, mentoring, strengthening capital as well as monitoring, coaching and evaluation. In addition, to improve product quality, more attractive packaging designs and online marketing are needed. The results of this PKM activity are as expected. This can be proven by the fulfillment of targets and the enthusiasm and enthusiasm of the partners when listening to / paying attention to the material presentation and processing practices, so that with this PKM activity the partner's income will increase.